Julian Robertson: A Tiger in the Land of Bulls and Bears - Daniel A Strachman (Wiley, 2004)
Julian Robertson is one of the most successful and well-known hedge fund managers of our time. For nearly twenty years his infamous fund--Tiger Management--was the talk of the town, routinely delivering double-digit performance. This biography will explore this legendary fund manager's role in the development and popularity of hedge funds, examine his investment methodology and strategy, and look at the growth of his fund and his 'Tigers'--individuals who have gone on to great success themselves. * Includes candid interviews of Robertson, his colleagues, and his peers * Uncovers the trading strategies and investment style of a legendary fund manager * Offers a rare glimpse inside the personal world of Julian Robertson